Induction of labor with prostaglandin E2 Oral - Gonzáles del Riego, Manuel (2015)
Induction of labor with oral prostaglandin E2 (PGE2) in 110 patients, succeeded in 100 vaginal births; there were 9 failures of induction and cesarean section, with an effectiveness rate of 90.9%. Resultdos analysis of 100 pregnant women with vaginal delivery is done: 53 were elective and 47 indicated; by post maturity (18 patients), dysfunctional labor (13), premature rupture of membranes (9), toxemia (5), diabetes (2). 86% had a single labor induction session without difference between elective and indicated. PGE2 was administered in doses of progressive time from 0.5 to 2 mg. The patients had clinical scoring MONITORING incidents related to stimulation, labor, delivery and newborns. Pelvic Bishop score was taken as a prognostic indicator of successful induction. 24.5% of elective inductions and 47% of the indicated higher scores were 7, considered very favorable. This indicator keeps indirectly related to the total dose of PGE2 necessary to achieve vaginal delivery and the total induction time; but not related to age, weight index of the mother or elective induction condition. 95 infants in severe hypoxia (Apgar 1) was presented; this was related to the uterine contraction disorders secondary to PGE2 administration. Maternal side effects, fever, nausea and diarrhea were mild.